Delayed presentation of isolated female epispadias with urinary incontinence: a case report - Adewale Olaotan Oyinloye; Samuel Wabada; Auwal Mohammed Abubakar; Christopher Uruku Rikin (SpringerOpen, 2022)
Abstract Background Female epispadias is a rare congenital anomaly, with a quoted incidence of 1 in 480,000.These patients present with urinary incontinence and varying degrees of external genitalia abnormality. This report presents the delayed presentation and management of a 14-year-old female with urinary incontinence due to isolated epispadias. Case presentation This is the case report of a 14-year-old female with urinary incontinence noticed since infancy. Examination of the genitalia revealed a bifid clitoris, depressed mons pubis, underdeveloped labia, patulous urethral opening, and normal vagina. She had surgical repair of the anomaly and has subsequently achieved continence. She has been continent in the last 4 ½ years of follow-up and is now married with a 1-year-old child. Conclusion Female epispadias is a rare but often missed cause of incontinence. A high index of suspicion and careful genital examination will help in identifying this anomaly. Surgical correction achieves satisfactory outcome as regards continence and cleanliness. Long-term follow-up is essential.